UJI LARUTAN MENIRAN (Phyllanthus niruri L) UNTUK PENGOBATAN IKAN LELE DUMBO (Clarias gariepinus) YANG TERINFEKSI BAKTERI Edwardsiellatarda - Jarod Setiaji; T Iskandar Johan; Agus Pramujiono (UIR Press, 2013)
Meniran (PhyllanthusniruriL) solution test for the treatment measures of Clariasgariepinus which was infected by bacteria Edwardsiellatarda was conducted. The purpose of this study was to find the effective concentration of the solution meniran for prevention of red spot disease (edwardseliosis) that infect catfish. The completely randomized design with 4 treatments and 3 replications was used. The treatment was worked by soaking in a solution with meniran concentrations of 3,000 ppm, 5,000 ppm, 7,000 ppm and without being given meniran solution as a control. The average of meniran solution inhibition against bacteria at concentration of 50,000 ppm of 14.3 mm, concentration of 25,000 ppm of 12 mm, concentration of 10,000 ppm of 8.7 mm and concentration of 5,000 ppm of 6 mm. Meniran L D50 concentration test of 40,000 and 60,000 on the 24-hour immersion caused death by 10%. The highest survival rate was found at a concentration of 7,000 ppm as 86.67%.